Three phase PUC5 inverter fed induction motor for renewable energy applications - V V Nagaraju Goriparthi; Gudapati Sambasiva Rao (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
This paper gives the overview three phase 5 level packed U cell (PUC5) inverter fed Induction Motor feed from renewable energy sources for electric vehicles and water pump set in agriculture applications. PUC5 inverter requires a minimum number of semiconductor devices, one PV panel and only one capacitor in each phase. Maximum all possible switching sequences are analyzed and sensor less voltage balancing technique depending on simple switching modes was integrated as level shifted PWM controller for control the PUC5 inverter switches. Sensor less voltage balancing fixes the capacitor voltage (Vc) at half of the PV source (Vdc) magnitude in each phase, which results the symmetric five level wave in phase voltage output and seven level waveform in line voltage with less harmonics. This topology minimizes the complication in the control system which creates the PUC5 inverter most suitable for industrial applications and market requirements. It is compared with other popular multilevel inverters In terms of component count, voltage rating, voltage balancing and complexity etc. In order to test the performance proposed PUC inverter it is tested with rated load with Matlab/Simulink. The results obtained have shown good dynamic performance under different conditions.